Pengujian Sifat Fisis Dan Kimia Air Tanah di Daerah Sentani Dan Sekitarnya - Bodian Davin Panggabean; Frans Simbol Tambing (Jurnal Sains dan Teknologi, 2023)
Communities in Jayapura use groundwater for their daily needs both from springs, dug wells and drilled wells. The research was conducted in the Sentani and surrounding areas. The purpose of this study was to determine the physical and chemical properties of groundwater based on laboratory tests. The physical and chemical properties of groundwater are one of the main properties of water and are very useful for determining the quality of groundwater. This study took three sampling locations with stratified random sampling method. The samples taken were springs, dug wells and drilled wells. The parameters of the physical properties of groundwater tested included pH, temperature ( T0C ), TDS, hardness ( CaCO3 ), while the parameters of the chemical properties of ground water tested included magnesium (Mg), calcium (Ca), potassium (K), Sodium (Na), Sulfate (SO4), Chloride (Cl) and Bicarbonate (HCO3). In general, all samples analyzed from the study area showed that the levels of chemical elements in groundwater had not exceeded the drinking water standard limits, but there were locations that had high levels of magnesium, namely location 1 (Sosiri) of 149 mg/L. The results of the physical properties test showed that the test content value had not exceeded the drinking water standard limit, in the sense that the groundwater in the study area was suitable for use.